SIMULATION OF PSYCHROMETRIC CHAMBER FOR RESIDENTIAL AIR CONDITIONER - Barari, Fajar
The usage of air conditioner in Indonesia is increasing anually. As a result, national electricity consumption rises because the electric consumption of air conditioner is high. To optimize the usage of electricity, Indonesian Ministry of Energy and Mineral Resources established standard energy efficient of air conditioner that regulated in Indonesian Ministry of Energy and Mineral Resources Regulation No. 57 of 2017. However, the numbers of psychrometric chamber which is used as testing facility is too few. Therefore, simulation of pyschrometric chamber is needed to eximine the design of psychrometric chamber. The purpose of this simulation is to obtain the prediction of psychrometric chamber’s characteristic and its duration to attain standard operation based on ISO 5151. Variation of parameters are simulated to observe effect of changes in conductivity, width of insulation and surrounding temperature toward power of compressor and heater to maintain desired conditions. Psychrometric chamber is modeled by mass balance and energy balance equations in transient state. This simulation is done by using Simulink. Operation condition based on ISO 5151 is achieved in 33 minutes, indoor TDB and TWB are 26.8 oC and 19.3 oC while outdoor TDB and TWB are 34.9 oC and 24.0 oC. Decreasing 1 cm of width of insulation resulting addition power of indoor compressor and outdoor heater of 2.46 W (0.05%) and 12.69 W (0.29%). Increasing 0.0062 W/m.K of thermal conductivity resulting addition power of indoor compressor and outdoor heater of 2.22 W (0.05%) and 11.42 W (0.27%). Increasing 2 oC of surrounding temperature resulting addition indoor compressor power of 19.5 W (0.44%) while reduction outdoor heater power of 45.53 W (1.07%).